1997
DOI: 10.1089/lap.1997.7.7
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Preperitoneal Herniorrhaphy in Professional Athletes with Groin Pain

Abstract: Groin pain in athletes is a difficult problem requiring a multidisciplinary approach to diagnosis and treatment planning. Endoscopic preperitoneal herniorrhaphy is an effective treatment for obscure groin pain when the pain is associated with an inguinal hernia and allows for a short recovery time back to full athletic activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
43
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 13 publications
2
43
0
Order By: Relevance
“…2,6,9,14,[22][23][24][25][26][27] Two articles focused on osteitis pubis confirmed on MRI or bone scan. 2,27 Eight studies 6,9,14,[22][23][24][25][26] investigated a total of 196 patients. From the 8 studies (Table 1), sixty-five percent were football players.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…2,6,9,14,[22][23][24][25][26][27] Two articles focused on osteitis pubis confirmed on MRI or bone scan. 2,27 Eight studies 6,9,14,[22][23][24][25][26] investigated a total of 196 patients. From the 8 studies (Table 1), sixty-five percent were football players.…”
Section: Resultsmentioning
confidence: 99%
“…6,9,14,23,24,26 The type of preoperative pain was not well described by any of the studies and was stated as being a dull ache or pulling sensation in 2 articles. 14,25 Pain was reported to occur at rest in 81% of patients 6,14,22,24 and had lasted between 2 and 13 months. 6,9,14,22,[24][25][26] Most studies reported an initial conservative approach incorporating measures such as rest, steroids, physiotherapy, hydrotherapy, and analgesics.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The history must include questions directed at referred lumbar abnormalities, including back pain, radiculopathy and sensory disturbances [1,2,6,16,[22][23][24]27]. Night pain and persistence of pain at the rest may indicate the presence of a neoplasm.…”
mentioning
confidence: 99%